Modelagem termomecânica do crescimento de pressão em anulares confinados em poços de petróleo na presença de evaporitos - Vasconcelos, Themisson dos Santos (2019)
Events resulting from the temperature increase associated or not with the creep in saline rocks can generate a significant pressure increase in annular spaces in oil wells. The phenomenon known in the petroleum industry as annular pressure build-up (APB) has become quite relevant today, given the vulnerability of occurrence in oil fields located in deep and ultra-deep Pre-salt areas, whose exploratory interest has increased significantly, given its productive potential. In this perspective, the present study aims to development and implement a multilayer one-dimensional axisymmetric thermomechanical model, aiming at numerically modeling and analyzing the APB phenomenon, considering the prescribed thermal increment and/or associated to the creep mechanism presented by the salt rocks. Two constitutive models are used to represent the rock formation, the linear elastic and the double deformation mechanism, which is used as a result of the good results when compared to in-situ responses. For the analysis of the displacement of the saline rock, a finite element model is developed that associates heat transfer phenomenon, through the weak thermomechanical coupling, with the double deformation mechanism to portray the thermal effect on the evaporites. The modeling developed also allows the inclusion or calculation of fluid-related properties, according to temperature and pressure conditions, iteratively dependent on the entire APB calculation process. In this conjecture, the calculations involved must deal with nonlinearities of constitutive models, fluid-structure interactions, and computer simulations applied to case studies. Case studies are developed and verified based on bibliographies on the proposed theme. The developed modeling contributes to the investigation of the pressure increase caused only by the influence of the saline rock or the prescription of the thermal increase in arrangement with the adopted constitutive models, having potential use for the prediction of efforts in the design and the begin of production phases of oil wells.